Current and New Perspectives on the Molecular and Cellular Mechanisms of Amyloid Formation and Toxicity in Light Chain Amyloidosis - DiCostanzo, Ara Celi; Ramirez-Alvarado, Marina (IntechOpen, 2011)
None